A Ritual Interrupted: A Case of Contested Ritual Practices in a Q'eqchi'-Maya Catholic Parish. Issue 3 (1st September 2016) - Hoenes del Pinal, Eric
Abstract: Although Q'eqchi'-Maya Mainstream Catholics and Charismatic Catholics in the Guatemala highlands share many of the same physical and social spaces, the relationship between them is a tense one due to their differing modes of ritual practice. Although this conflict rarely comes to a head directly, on one particular occasion a highly ranked member of a Mainstream congregation, and indeed an outspoken critic of the Charismatics, entered the village chapel during the latter's weekly service and proceeded openly to criticize their ritual practices, leaders' religious knowledge, and relationship to the larger institutional Catholic Church. This article analyzes this event as a means of furthering our understanding of what happens when unexpected circumstances threaten the integrity of a religious group's ritual. How do participants try to circumvent, mitigate or otherwise manage such an occurrence? Examining the spoken and embodied actions taken by both the speaker criticizing the congregation and his intended audience sheds light on the interactive strategies each used to manage their social and ethical standing during the uneasy interaction. This article draws critical attention to the way adherents to two related but distinct forms of Christianity establish and contest their modes of religious authority through language, discourse, and bodily behavior. By investigating an episode in which two modes of Christian practice came into direct confrontation with each other, we can better understand how differing ways of being Christian are dialogically constituted.